Normative and anthropological grounds of etiquette (I. Kant and N. Elias) - Rohozha, Mariya (Ukrainian Cultural Studies, 2024)
Background. The article researches etiquette as a phenomenon of the Western culture in normative and anthropological dimensions, basing on the ideas of practical anthropology (empirical ethics) by Immanuel Kant and sociogenetic studies by Norbert Elias.Methods. General scientific methods of analysis and synthesis are used to define the normative and anthropological grounds of etiquette in the concepts of the mentioned thinkers. The specificity of the study presupposes the interdisciplinarity in involving philosophical (ethical) and cultural approaches in understanding the specified issues.Results. Kant's conceptualization of the regulation of proper conduct is carried out within empirical ethics. He defined real rules of conduct that a person has to follow in morally meaningful life. He precisely focused on good manners, which possess individual and social value despite the fact that they are often only "decent illusions" that camouflage passions and indecencies. Elias, in his reflections on good manners, was focused on defining the quality of their transformations in the course of cultural and historical progress. Based on Elias's concept of "conditioning" as the adaptation of individuals to standard modes of behavior, the author of the article demonstrates from which irrational sources good manners are born, how they are disseminated and implemented.Conclusions. Gallant manners acquired ritualized forms at the absolutist court, breaking away from their material grounds. The transformation of external constraint in following good manners into self-constraint became possible in the development of civilization and the weakening of external threats. The initial copying of gallant manners by representatives of the bourgeoisie and their subsequent widespreading in the Western European public space led to the democratization of this phenomenon. Such logic is characteristic of civilizational progress and does not work in conditions of reduction of the social state to the natural one in emergency situations.
Keywords: etiquette; I. Kant; N. Elias; good manners; virtues; conditioning; practical anthropology; normative regulation